Pengaruh Kinerja ICSR Terhadap Readability ICSR Menggunakan Gunning Fog Dan Flesch-Kincaid Indeks Dengan Size, Kinerja Keuangan, Leverage Dan Growth Sebagai Variabel Kontrol - Riyang Mardini (Universitas Islam Bandung, 2020)
Islamic Corporate Social Responsibility is an assimilation of social responsibility that must be considered by Islamic banking in Indonesia. Islamic Corporate Social Responsibility has experienced an increase in demand from various stakeholders, this condition is the reason for Islamic banking to improve the performance of Islamic Corporate Social Responsibility and communicate it to stakeholders. In presenting its social responsibility to the public, Islamic banking is expected to provide communicative, simple, quality, and easy-to-understand information. This study investigates the effect of the performance of Islamic Corporate Social Responsibility on the readability of Islamic Corporate Social Responsibility. Size, financial performance, leverage and growth as control variables in this case. The results of the study state that the Islamic Corporate Social Responsibility performance affects the readability of Islamic Corporate Social Responsibility.